A Novel Paradigm to Design Personalized Derived Images of Art Paintings Using an Intelligent Emotional Analysis Model - Duan, Yingjing; Zhang, Jie; Gu, Xiaoqing (Frontiers in Psychology, 2021)
With the development of artificial intelligence, it is imperative to combine design methods with new technologies. This paper from the perspective of personalized design of art paintings’ derived images, analyzes the new user demand generated by the current situation and background of personalized design, puts forward a new method of derivative design based on artificial intelligence emotion analysis, and verifies the feasibility of the new method by constructing a personalized design system of art paintings’ derived images driven by facial emotion features, explores the method of combining artificial intelligence emotion recognition, emotion analysis and personalized design, which provides new ideas for the design of art derivatives for the future with massive personalized demand. It is thinking and practicing from the perspective of the development of new technology to promote the change of design paradigm in the digital age.